2014
DOI: 10.3354/meps10912
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification rapidly reduces dinitrogen fixation associated with the hermatypic coral Seriatopora hystrix

Abstract: Since productivity and growth of coral-associated dinoflagellate algae is nitrogen (N)-limited, dinitrogen (N 2 ) fixation by coral-associated microbes is likely crucial for maintaining the coral−dinoflagellate symbiosis. It is thus essential to understand the effects future climate change will have on N 2 fixation by the coral holobiont. This laboratory study is the first to investigate short-term effects of ocean acidification on N 2 fixation activity associated with the tropical, hermatypic coral Seriatopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…This input of new fixed nitrogen into the reef ecosystem helps to sustain net productivity under oligotrophic conditions and to compensate for net nitrogen export from the system, for instance by currents [44]. Nitrogen fixation in hermatypic corals has been reported for several different species [45][46][47][48], suggesting a high relevance of this process for the coral holobiont. However, reported nitrogen fixation rates in corals are about a magnitude lower than those found in reef sediments and bare rock [43].…”
Section: Nitrogen Fixationmentioning
confidence: 97%
See 2 more Smart Citations
“…This input of new fixed nitrogen into the reef ecosystem helps to sustain net productivity under oligotrophic conditions and to compensate for net nitrogen export from the system, for instance by currents [44]. Nitrogen fixation in hermatypic corals has been reported for several different species [45][46][47][48], suggesting a high relevance of this process for the coral holobiont. However, reported nitrogen fixation rates in corals are about a magnitude lower than those found in reef sediments and bare rock [43].…”
Section: Nitrogen Fixationmentioning
confidence: 97%
“…It is thus likely that similar regulatory mechanisms to reduce nitrogen fixation rates at times of excess nitrogen availability exist in coral-associated diazotrophs ( Figure 1). Nitrogen fixation activity in corals is highly dynamic and can be rapidly affected by changes in environmental conditions [46,48]. Consequently, nitrogen fixation may serve as a mechanism to counteract shortages of environmental nitrogen availability, and maintain a constant nitrogen supply for symbiont-based primary production in corals.…”
Section: Nitrogen Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Davey et al (2008) showed that coral death as a result of thermal bleaching enhanced N 2 fixation through production of organic matter followed by the decay of coral tissue, which induced an increase in the development of microbial epiphytic and epilithic communities on coral skeletons. Finally, a recent study showed that low pH (decreased pCO 2 ) significantly decreased N 2 fixation associated with some coral species, likely due to a competition for energy between coral calcification or photosynthesis and N 2 fixation (Rädecker et al, 2014). Taken altogether, these observations suggest that more studies have to be undertaken to assess N 2 fixation rates in reefs under diverse environmental conditions, including climate change ones, because most of the knowledge comes from other systems and cannot be always applied to reef diazotrophs.…”
Section: N 2 Fixation In Coral Reef Ecosystems Description Of N 2 Fixmentioning
confidence: 99%
“…In such a scenario, it is likely that nutrient-limited corals will increasingly rely on DDN to meet their nitrogen metabolic requirements. Conversely, increased pCO 2 has been reported to decrease coral-associated N 2 fixation, suggesting that nitrogen starvation of the coral host may exacerbate the long-term effects of ocean acidification (Rädecker et al, 2014). Although we are just beginning to understand the effect of single stressors on N 2 fixation, additional multiple stressor studies are needed to assess synergistic or antagonistic climate change effects on coral-associated N 2 fixation and its responsible diazotroph communities.…”
Section: Does Diazotrophy Enhance Coral Resilience?mentioning
confidence: 99%